Real-life economics understanding wealth creation - edited by Paul Ekins (London Routledge, 1992)
The past fifty years have witnessed the triumph of an industrial development that has engendered great social and environmental costs. Conventional economics has too often either ignored these costs or failed to analyse them appropriately. This book constructs a framework within which the wider impacts of economic activity can be both understood and ameliorated. The framework places its emphasis on an in-depth understanding of real-life processes rather than on mathematical formalism, sressing the independence of the economy with the social, ecological and ethical dimensions of human life.
Includes bibliographical references (p. [431]-450) and index.
Keywords: Economics